'Mat Rempit' - looking at the contemporary road transport act 1987 (act 333) / Zainal Abdul Hamid, Nik Hassanuddin Mohd Ghazali - Abdul Hamid, Zainal; Mohd Ghazali, Nik Hassanuddin (2008)
This research aims to analyze the existing law in curbing the 'Mat Rempit' menace in Malaysia and to examine whether there are other existing laws that may be used. Practically every major state or districts in Malaysia have been waging war against these "Mat Rempit', who have been known to be a nuisance on our roads and notoriously involved in gang robberies, rape and even murder. Therefore this research will focus and examine the effectiveness of the Road Transport Act 1987 in eradicating this menace of 'Mat Rempit'. Statistics from 2002 to 2006 have shown an accerating rise in the number of cases involving these 'Mat Rempit'. Besides the Road Transport Act 1987, this research will also consider various other statutory provisions in other relevant statute that may be use to curtail the lack of effectiveness in the provision of the Road Transport Act 1987 in order to suppress the menace of 'Mat Rempit'.